Schenkerian Theory, Neo-Riemannian Theory and Late Schubert: A Lesson from Tovey - Rusch, René (Journal of the Society for Musicology in Ireland, 2013)
Current analytical studies on Schubert’s tonality have tended to favour either Schenkerian theory or, more recently, neo-Riemannian theory to explain the composer’s signature harmonic progressions. What remains unclear with respect to these two prevailing analytical purviews is the extent to which one may relate to the other. This article offers a new way of understanding how Schenkerian and neo-Riemannian views of Schubert’s late tonal practices may be complementary, using Tovey’s concept of key-relations from his article ‘Tonality in Schubert’ of 1928. It suggests that Tovey’s key-relations can function as a bridge between these two theories because they approximate parsimonious voice-leading operations while preserving chord function within a tonal hierarchy. In forming an intermediate pathway between Schenkerian diatony and neo-Riemannian theory’s parsimonious voice-leading operations, Tovey’s key-relations highlight the important contributions that Schenkerian theory and neo-Riemannian theory offer to our understanding of Schubert’s tonality.